Women and the travel guidebook, 1870-c.1910 - Proteau, J (2021)
Despite the large printing giants of John Murray and Karl Baedeker dominating the nineteenth-century travel guidebook market, women were important producers and consumers of travel guidebooks between 1870–c.1914. My thesis argues that in the late nineteenth century, women were key cultural producers of travel guidebooks, an important form of non-fiction mass media, during an upsurge and shift in European travel and tourism. While a few studies have identified a small number of female-authored guidebooks, this is the first to take a broad view of women’s place within the guidebook market, situating female-authored texts within a large and competitive book market to understand the role of gender in guidebook publication. Like the guidebooks it focuses on, this thesis is interdisciplinary in nature. It straddles book and publishing history, women’s history, the history of travel, and cultural history. Drawing on Robert Darnton’s theory of the communications circuit which considers the roles of the author, publisher, bookseller, and readers in the production of print as circular and emphasizes the system as a holistic process, this thesis investigates the role of women as both readers and writers of guidebooks. I argue that the line between the role of writer and reader was often blurred. My thesis also draws from Georg Simmel’s theory of the web of group affiliations to stress the significance of social networks to women’s guidebook writing, as well as to argue for the inclusion of some among those examined into the framework of intellectual aristocracy, expanding this group beyond the predominantly male and England-focused studies of Noel Annan and William Whyte.